Planning and Implications of Social Media Tools to Provide Quality Library Services in Academic Libraries - Patel, Umesh A (Journal of Advanced Research in Library and Information Science, 2021)
The core objective to work in this domain is to address how one can exploit the social media to serve the purpose of providing modernize library and information services in context of present digitized society. This study is based on selected research samples which are fifty regular library users from five different and premier engineering colleges stationed within the region of central Gujarat. This paper concluded that good quality libraries are using social media such as Facebook, whatsapp and LinkedIn in a wider way to provide its continuous services to its esteemed users. All most all the libraries utilizes the social media route the most effective and easy to reach to general masses to highlight their library product, services, events, advertisement, research purposes and video conferencing. The online questionnaire was floated to the aforementioned library personals and received the same with their feedback, opinion and suggestions indication how to make library services more attractive and usable by utilizing social media platform effectively and efficiently.